THE MEANING OF BEAUTY AS INSPIRATION AND MOVEMENT OF CHANGE IN THE “BEAUTY MOVES YOU” VERSION OF WARDAH ADVERTISEMENT - Ahmad Yazid Lubis; Lina Maurissa; Ocvita Ardhiani (Universitas Gunadarma, 2022)
This study aims to explore the meaning of beauty as an inspiration and movement of change for Indonesian women in the Wardah advertisement version of